Disability equality and discrimination in higher education: staff and student perceptions of the 'reasonable' adjustments made for print disabled students - Rowlett, Emma Jane (2011)
The aim of this research was to explore staff and student experiences of the barriers print disabled students face and the adjustments made to overcome these. Universities are obliged by the Special Education Needs and Disability Act 2001 and the Disability Discrimination Acts 1995 and 2005 to make 'reasonable' adjustments, but receive only limited guidance as to how far they have to go to do this.